(3YbjdI GdOef GdeNJUQ ef CfHGA GdRef aj CNHGQ Gdjefs - (3jMji Hf GdMSjf Hf GdbGSe Hf eMeO, GHf GdbGpSe,J (B1099 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYRjR GdbgGQ GdgGOi Edi GdEYJHGQ s
(3BNQgG (B:s
(3hjfJgi HGdcdGe Ydi MhGOK hhajGJ SfI (B1045(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B143 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B192s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B109 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs